ENVIRONMENTAL AND BEHAVIORAL CONDITIONS THAT AFFECT MALARIA EVENTS IN PADANG CITY - Masrizal Masrizal; Tria Syananda Putri; Imraatul Hasni (Jurnal Berkala Epidemiologi, 2020)
Background: West Sumatra is a target area for malaria elimination in 2020; the Annual Parasite Incidence (API) in Padang City increased from 0.12 per 1000 inhabitants to 0.13 per 1000 inhabitants between 2015 and 2016. Purpose: This study aimed to analyze the effect of factors contributing to malaria events based on the environmental and behavioral conditions of people in Padang City. Method: This is a quantitative study using a case-control approach. The research was conducted in Padang from August 2017 until January 2018. The case-control study was conducted on a sample of 62 people, consisting of 31 cases and 31 controls. Cases were identified through random sampling and controls were selected by purposive sampling. Data collection was via observation and questionnaires and both univariate and bivariate analyses were conducted. Results: Descriptively, malaria patients were more likely to live in at-risk physical conditions at home (74.12%), had a history of visiting endemic areas (41.90%), did not use mosquito repellent equipment (58%), and had the habit of being outdoors at night (32.28%). Statistical tests showed the risk factors for the incidence of malaria were the physical condition of the house (OR = 3.43; 95% CI 1.20–9.20) and a history of visiting endemic areas (OR = 9; 95% CI 1.20–394). Conclusion: Environmental and behavioral factors affect the incidence of malaria. It is recommended that the Padang City Health Office provide counseling through health promotion officers about healthy homes and advise people not to go to endemic areas.